2023
DOI: 10.3389/fped.2023.1131629
|View full text |Cite
|
Sign up to set email alerts
|

Impact of donor age on short-term outcomes after pediatric split liver transplantation

Abstract: BackgroundDonor shortage is an important limitation of liver transplantation (LT). Split liver transplantation (SLT) may increase the sources of donors and reduce the problem of organ shortage. However, there are no standard criteria of the selection of SLT donor, especially regarding the donor age.MethodsWe retrospectively analyzed the clinical data of children who received initial SLT between January 2015 and December 2021. Based on the age of donors, the patients were divided into groups A (1–10 years old; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…With rigorous donor condition screening and meticulous recipient selection, employing liver grafts from donors aged 55 years for SLT can also yield favourable outcomes. There are no statistically significant differences in outcomes compared with liver grafts from donors in the standard age group (<50 years) 26 . Furthermore, if the donor has not received vasopressor treatment or has only received low‐dose vasopressor treatment once, and the graft‐to‐recipient weight ratio (GRWR) is within the range of 2%–4%, using liver grafts from donors younger than 7 years for SLT can still yield favourable treatment outcomes 27…”
Section: Split Liver Transplantationmentioning
confidence: 99%
“…With rigorous donor condition screening and meticulous recipient selection, employing liver grafts from donors aged 55 years for SLT can also yield favourable outcomes. There are no statistically significant differences in outcomes compared with liver grafts from donors in the standard age group (<50 years) 26 . Furthermore, if the donor has not received vasopressor treatment or has only received low‐dose vasopressor treatment once, and the graft‐to‐recipient weight ratio (GRWR) is within the range of 2%–4%, using liver grafts from donors younger than 7 years for SLT can still yield favourable treatment outcomes 27…”
Section: Split Liver Transplantationmentioning
confidence: 99%
“…Ding et al [ 12 ] previously reported that out of 11 liver grafts, only 2 (18.2%) underwent ex-vivo splitting. Similarly, Xu et al [ 13 ] performed only 20 (14.3%) SLT procedures out of the 140 liver transplantations.…”
Section: Introductionmentioning
confidence: 99%